2009
DOI: 10.1038/nature07879
|View full text |Cite
|
Sign up to set email alerts
|

Electromotive force and huge magnetoresistance in magnetic tunnel junctions

Abstract: The electromotive force (e.m.f.) predicted by Faraday's law reflects the forces acting on the charge, -e, of an electron moving through a device or circuit, and is proportional to the time derivative of the magnetic field. This conventional e.m.f. is usually absent for stationary circuits and static magnetic fields. There are also forces that act on the spin of an electron; it has been recently predicted that, for circuits that are in part composed of ferromagnetic materials, there arises an e.m.f. of spin ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
111
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 18 publications
1
111
0
5
Order By: Relevance
“…The experiments that have observed SMF so far are all done in FMs [15][16][17][18][19]. A question naturally arises; can one expect SMF in materials with different magnetic orderings from FM, such as antiferromagnets (AFMs) [20][21][22]?…”
mentioning
confidence: 99%
“…The experiments that have observed SMF so far are all done in FMs [15][16][17][18][19]. A question naturally arises; can one expect SMF in materials with different magnetic orderings from FM, such as antiferromagnets (AFMs) [20][21][22]?…”
mentioning
confidence: 99%
“…It is also worth pointing out that even for the situations in which the phase separation can lead to important technological application 19 the role of the influence of strain on the phase diagram is an important study, since the composition of these second phases can change if the phase diagram changes, 20 which means that if there is some influence of the strain on the spinodal decomposition it will also have some influence on these embedded nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the conduction of MNFs is controlled by quantum electron tunnelling effects [3][4][5][6][7] . Theoretical studies of…”
Section: Introductionmentioning
confidence: 99%